General versus Specific Skills in Labor Markets with Search Frictions and Firing Costs - Wasmer, Etienne (American Economic Review, 2006)
Human capital investments are not independent of the aggregate state of labor markets: frictions and slackness of the labor market raise the returns to specific human capital investments relative to general investments. We build a macroeconomic model with two pure strategy regimes. In the pure G-regime, workers invest in general skills. This occurs when they face high turnover labor markets and in the absence of employment protection. The pure 5-regime in which workers invest in skills specific to their job appears when employment protection is high enough. Implications for a characterization of Europe-United States differences are provided in conclusion.